Teachers' Contributions in Child-Friendly Schools at State Elementary School 106796 through Anti-Bullying Activities for the 2023/2024 Academic Year - Ismi Azmi (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
The aim of this research is to: (1) identify bullying behavior occurring in Grade IV at SD Negeri 106796, (2) analyze the factors contributing to bullying behavior, (3) examine the impact of bullying, and (4) explore teachers' contributions in implementing an anti-bullying program at SD Negeri 106796. This study employs a qualitative descriptive approach using a case study method. The data sources include the school principal, homeroom teacher, students as victims, and students as perpetrators. Data collection techniques consist of observation, interviews, and documentation. The data were analyzed through reduction, data presentation, and conclusion drawing. The findings indicate that teachers play a crucial role in addressing bullying behavior among Grade IV students by implementing an anti-bullying program. This program involves developing a system to prevent and handle bullying cases, stopping violent acts at school, conducting training on positive discipline methods for teachers, providing anti-bullying counseling, and fostering a child-friendly school environment. Additionally, teachers implement disciplinary measures such as punishments and rewards, form study groups, offer guidance and reinforcement to students, and establish information services related to bullying prevention.